REACH a munkahelyen : milyen elónyök származnak a munkavállalóknak a vegyszerkkel kapcsolatos új európai politikából? - Musu, Tony (Brussels, 2004)
"The proposed reform of the European legislation on trade in chemical substances, known as REACH (Registration, Evaluation and Authorisation of CHemicals), pursues two main aims: ensuring a high level of protection for human health and the environment; and strengthening the competitiveness of the European chemical industry. European workers stand to benefit enormously from this reform, since at present the manufacture and use of chemicals in the workplace takes a heavy toll on them. Indeed, approximately one out of every three occupational diseases recognised annually in Europe can be ascribed to exposure to hazardous chemicals. In order to better understand in what way the REACH reform represents a real opportunity to reduce the number of occupational diseases related to exposure to dangerous substances, this publication begins by examining the reasons why a reform is needed; it then describes the content of the REACH reform and the changes it will make to the existing legislation. It concludes by explaining the state of play in the legislative process underway at the European Parliament and the Council, which should result in the adoption of the REACH Regulation."